CONTEMPORARY SPORTS: PROBLEMS AND SOLUTIONS - Sotivoldiev Qodirjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Contemporary sports are a powerful industry that includes special system of sports record achievement. It involves sportsmen and coaches as well as managers, doctors in sports medicine, psychologists and research associates. Mass media keep on promoting extensive competitions as main events of social life. Nevertheless, contemporary sports should not be treated as a unified phenomenon that has one goal, functions and common patterns of development. Contemporary sports have many faces and varieties. Sports system includes such kinds as mass sports, children and youth sports, school sports and students sports that solve the problems of health promotion and sports education of the youngsters. High-performance sports (Olympic and professional sports) are aimed at achieving high results and victories. All these kinds are united by common functions: spectacular, political and economic. High-performance sports provide a special lifestyle and way of being successful, showing great sports style and the ability to see off the challenger. Many spectators take it as a role model not only in sports but also in other sectors of life. However, high-performance sports have created many contradictions that do not allow contemporary sports to develop positively, often discredit them and contribute to people’s, especially parents’, attitude that sports are not good. Public opinion tends to consider contemporary sports to be dangerous activities. Research objective: to carry out a sociologic analysis of contradictions in contemporary sports and to offer ways of overcoming them.